PENGARUH KOMPETENSI SARJANA AKUNTANSI, REGULASI PEMERINTAH DAN ETIKA PROFESI TERHADAP KEMAMPUAN SARJANA AKUNTANSI UNTUK BERSAING DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Eva Puspitasari; Noor Shodiq Askandar; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis research was conducted to analyze "the influence of the competence of undergraduate accounting, government regulation and professional ethics on the ability of undergraduate accounting in facing the era of industrial revolution 4.0". The samples in this study were Accounting Graduates of the Faculty of Economics and Business, Islamic University of Malang, Malang State University, Muhammadiyah University of Malang and State Islamic University of Maulana Malik Ibrahim Malang. The analytical method used is Multiple Linear Regression with SPSS 22 For Windows software. Based on the results of simultaneous hypothesis testing shows that simultaneously the competencies of undergraduate accounting, government regulation and professional ethics affect the ability of undergraduate accounting to compete in the era of industrial revolution 4.0. Partially, it shows that the competencies of undergraduate accounting, government regulation and professional ethics influence the ability of accounting graduates to compete in the face of the 4.0 industrial revolution era. Keywords: Bachelor of Accounting Competence, Government Regulation and Professional Ethics, Bachelor of Accounting Capability, Compete against the era of Industrial Revolution 4.0.